The Correlation of Students Digital Reading Attitude and their Reading Comprehension at 3rd Semester of English Education Department in UIN Bukittinggi - Alvianis, Fara; Safitri, Loli; Eliza, Eliza; Syafitri, Widya (Pusdikra Publishing, 2025)
This research aimed to investigate the correlation between students’ digital reading attitude and their reading comprehension at the third semester of the English Education Department at UIN Bukittinggi. The study employed a quantitative correlational design involving 54 students as the sample. Data were collected using a digital reading attitude questionnaire adapted from Putman’s reading attitude model and a reading comprehension score obtained from a validated reading test. The data were analyzed using descriptive statistics and Spearman’s rho correlation due to the non-normal distribution of the data. The findings indicated that students’ digital reading attitude obtained a mean score of 59.85, while their reading comprehension achieved a mean score of 83.2. The correlation analysis revealed a positive correlation between digital reading attitude and reading comprehension (r = 0.294, p < 0.05). These results indicate that students’ digital reading attitude is associated with their reading comprehension. Therefore, integrating digital reading materials and strategies into English instruction is recommended to support students’ reading comprehension development.